2019
DOI: 10.13075/ijomeh.1896.01323
|View full text |Cite
|
Sign up to set email alerts
|

Occupational burnout and its overlapping effect with depression and anxiety

Abstract: Objectives: The problem of defining burnout concerns its overlapping effect with other syndromes and disorders, such as depression and anxiety. Additionally, some individual characteristics influence susceptibility to burnout (e.g., neuroticism). Therefore, the question arises whether burnout is or is not a distinct syndrome. The aim of the study is to compare 2 distinct burnout measures by analyzing their connections with organizational and individual variables. Material and Methods: The study was conducted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
50
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 34 publications
(42 reference statements)
10
50
0
9
Order By: Relevance
“…As stated by the European Agency for Safety and Health at Work (EU-OSHA, 2018, 2019a, stress has become one of the most important psychosocial risks in the workplace, and it is crucial to develop measures to prevent it. Moreover, anxiety and depression are increasing (OECD, 2019) and are related to distress and burnout, which increases the difficulty of identifying and distinguishing these psychological problems (Bianchi et al, 2015;Golonka et al, 2019;Koutsimani et al, 2019;Bianchi, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated by the European Agency for Safety and Health at Work (EU-OSHA, 2018, 2019a, stress has become one of the most important psychosocial risks in the workplace, and it is crucial to develop measures to prevent it. Moreover, anxiety and depression are increasing (OECD, 2019) and are related to distress and burnout, which increases the difficulty of identifying and distinguishing these psychological problems (Bianchi et al, 2015;Golonka et al, 2019;Koutsimani et al, 2019;Bianchi, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, burnout can be a long-term process of resource depletion and inadequate responses to chronic job stress (Maslach et al, 2001;Schaufeli, 2017). Burnout is difficult to distinguish from depression since they share similar symptoms (Bianchi et al, 2015;Golonka et al, 2019;Koutsimani et al, 2019;Bianchi, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As an in uential treatment position, hospitals play an irreplaceable role in the epidemic response and prevention. As of February 28, more than 90 national-level and provincial-level medical teams, about 13,000 high-level health-care workers were gathered in Wuhan to collaborate with local medical staff to treat patients jointly [4]. Healthcare workers, especially the "front line "medical caregivers, witness the pain and suffering of the patients in their daily work [5].…”
Section: Introductionmentioning
confidence: 99%
“…On May 28,2019, the World Health Organization (WHO) declared in the 11th revision of the International Classi cation of Diseases (ICD-11) that burnout is a "professional phenomenon", and it is a syndrome caused by "chronic workspace stress that has not been successfully managed" [12]. Studies show that burnout is related to a series of self-reported physical and psychological stress indicators such as anxiety and depression [13], fatigue [14]. This situation should be taken seriously.…”
Section: Introductionmentioning
confidence: 99%
“…Burnout occupies a special place given the persistent difficulty in defining and classifying this concept [8]. Recently, the WHO organization classified burn out as a problem associated with employment or unemployment and as a factor influencing health status [9].…”
Section: Introductionmentioning
confidence: 99%